Comparison of employment among people with Multiple Sclerosis across Europe. Issue 2 (April 2022) - Ellenberger, David; Parciak, Tina; Brola, Waldemar; Hillert, Jan; Middleton, Rod; Stahmann, Alexander; Thalheim, Christoph; Flachenecker, Peter
Background: People with Multiple Sclerosis (PwMS) suffer from an increased risk of unemployment during the course of the disease. In recent years progress has been made in increasing the time until patients have to leave the workforce permanently. Such a retirement is often associated with MS but the driving factors including disability progression, support measures at the workplace, and societal aspects are not yet fully understood. Methods: We consolidated data from four European MS databases from Germany, Poland, Sweden, and the United Kingdom, which were able to provide data on working status, disability progression and quality of life in accordance with the data harmonization framework of the EUReMS (European Registry in Multiple Sclerosis) project. Results: Factors strongly associated with unemployment are disability progression, low quality of life and being close to the statutory retirement age. Overall, highest employment rate (77%) and lowest effects of gender and disease duration were found in Sweden. Conclusions: We found remarkable differences between the European registers and the countries studied, which may indicate inequalities at European level. Furthermore, our findings suggest that it is feasible and useful to combine data from different MS registers in Europe, albeit the data structures are heterogeneous.